Fooled by the fragments: vitamin B12 deficiency masquerading as thrombotic thrombocytopenic purpura. Issue 3 (4th May 2021) - Jahangiri, Pegah; Hicks, Rachel; Batth, Prabjot K.; Haas, Christopher J.
ABSTRACT: Background : Thrombotic thrombocytopenic purpura (TTP) is a hematological emergency requiring prompt plasmapheresis. Conversely, vitamin B12 deficiency is a relatively benign diagnosis that can mimic microangiopathic hemolytic anemia, characterized by the presence of anemia, thrombocytopenia, indirect hyperbilirubinemia, markers of hemolysis, and schistocytes. This case series highlights the association of vitamin B12 deficiency and its TTP-like presentations. Cases : The first case describes a 72-year-old man with shortness of breath and weakness. Diagnostics were notable for pancytopenia, schistocytes, and a low reticulocyte index. Intriguingly, total bilirubin was only mildly elevated however LDH and Haptoglobin were elevated and low, respectively. Additional diagnostic workup demonstrated an undetectable B12, elevated methylmalonic acid and elevated homocysteine. Initiation of B12 supplementation resolved his pancytopenia. The second case describes a 57-year-old man with chest tightness, dyspnea on exertion, and night sweats. Diagnostic evaluation demonstrated pancytopenia, schistocytes, a low reticulocyte index, and a remarkably low B12. He had associated high methylmalonic acid and homocysteine levels, confirming the diagnosis. B12 supplementation resolved his pancytopenia. Conclusion : The polysymptomatic presentation of vitamin B12 deficiency-induced pseudothrombotic microangiopathy highlights the vitamin's role in essential physiological cellular functions. Rapid recognition of the underlying etiology of microangiopathic hemolytic anemia is necessary as treatment approaches diverge greatly.